ASPEK SOSIAL EKONOMI TERKAIT MINAT IBU DALAM PEMILIHAN KONTRASEPSI - Kusumawardani, Emi; Yuliawati, Dwi; Silfiana, Andi; Tira, Deviarbi Sakke (Ensiklopedia of Journal, 2024)
Abstract: The choice of contraceptive method in family planning program is one of the important steps that can affect the success of controlling the number of births in the family. Based on data search, one of the community health centers in Semarang City that has many family planning participants who use injectable contraceptives is the Bandarharjo Community Health Center. Family planning participants in Bandarharjo Health Center tend to prefer injectable contraceptives over other types of contraceptives. The purpose of the study was to determine the relationship of socioeconomic aspects related to maternal interest in contraceptive selection. The research design used in this study was cross sectional. The research was conducted in the Bandarharjo Health Center working area. The research was conducted in October 2023. The study population was all mothers who used injectable contraceptives at the Bandarharjo Semarang Health Center in 2022 from January to December as many as 100 people. The research sample amounted to 100 respondents who were determined using total sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed there was a relationship of husband's support (p value: 0.045) and no relationship of employment (p value: 0.694) to the mother's interest in contraceptive selection. It is suggested that health services can increase the frequency of counseling related to contraceptives, especially injectable birth control by involving husbands so as to provide understanding and make acceptors choose contraceptives more rationally. For family planning acceptors to be able to explore the needs of family planning acceptors and accept if acceptors want to consult the needs of family planning in the family.Keywords: Husband support, contraception, employment.